Realization of Polaritonic Topological Charge at Room Temperature Using Polariton Bound States in the Continuum from Perovskite Metasurface. Issue 6 (15th January 2022) - Dang, Nguyen Ha My; Zanotti, Simone; Drouard, Emmanuel; Chevalier, Céline; Trippé‐Allard, Gaëlle; Amara, Mohamed; Deleporte, Emmanuelle; Ardizzone, Vincenzo; Sanvitto, Daniele; Andreani, Lucio Claudio; Seassal, Christian; Gerace, Dario; et al.
Abstract: Exciton‐polaritons are mixed light–matter excitations resulting from the strong coupling regime between an active excitonic material and photonic resonances. Harnessing these hybrid excitations provides a rich playground to explore fascinating fundamental features, as out‐of‐equilibrium Bose–Einstein condensation and quantum fluids of light, plus novel mechanisms to be exploited in optoelectronic devices. The formation of exciton‐polaritons arising from the mixing between hybrid inorganic–organic perovskite excitons and an optical bound state in a continuum (BIC) of a subwavelength‐scale metasurface, are experimentally investigated at room temperature. These polaritonic eigenmodes, hereby called polariton BICs (pol‐BICs) are revealed in reflectivity, resonant scattering, and photoluminescence measurements. Although pol‐BICs only exhibit a finite quality factor bounded by the nonradiative losses of the excitonic component, they fully inherit BIC peculiar features: a full uncoupling from the radiative continuum in the vertical direction, which is associated to a locally vanishing farfield radiation in momentum space. Most importantly, the experimental results confirm that the topological nature of the photonic BIC is perfectly transferred to the pol‐BIC. This is evidenced by the observation of a polarization vortex in the farfield of polaritonic emission. The results pave the way to engineer BIC physics of interacting bosons and novel room temperature polaritonic devices. Abstract : Polariton bound states in the continuum (pol‐BICs) are experimentally demonstrated at room temperature in excitonic metasurface based on 2D halide perovskite. These hybrid light–matter states exhibit all peculiar features of BICs: a total uncoupling from the radiative continuum associated to an infinite radiative quality factor, and a topological charge associated to a polarization singularity in the farfield emission.